Nonlinear Brownian motion – mean square displacement - Ebeling, W. (Condensed Matter Physics, 2004)
The stochastic dynamics of self-propelled Brownian particles is studied by
means of the Langevin and the Fokker-Planck approach. We model the
driving by a nonlinear friction function which has a negative part at small
velocities, leading to active Brownian motion of the particles. The mean
square displacement is estimated analytically and compared with numerical
simulations. Досліджується стохастична динаміка саморухомих броунівських частинок в рамках формалізмів Ланжевена та Фоккер-Планка. Рушійна сила моделюється нелінійною функцією тертя, яка має від’ємні значення при малих швидкостях, що приводить до активного броунівського руху частинок. Середньоквадратичне зміщення частинок оцінюється аналітично та порівнюється з даними чисельних розрахунків.